Transportation Route Selection Analysis of The Tuban-Bojonegoro Route Due to The Damage of The Glendeng Bridge - Mushthofa, Mushthofa (Journal of Green Science and Technology, 2023)
A bridge is a structure built to connect two or more points separated by a river, valley, ravine, or highway. Damage to a bridge can cause several adverse impacts, including: traffic accidents, transportation disruptions, economic disruptions, social disruptions, environmental damage, financial losses. The traffic flow diversion through the three-way intersection before the Glendeng Bridge to the Kaliketek Bridge is intended for small vehicles while large vehicles are diverted to the Soko-Ponco highway. The 4 km traffic diversion route is quite far for the local community. Apart from the Kaliketek Bridge alternative, people can also use boat crossings as access between cities. But the boat can only be used by two wheels. Therefore this study aims to determine the effectiveness of alternatives between Kaliketek routes and boat crossings. The purpose of this research is to analyze which path is more effective for 2-wheeled riders between the Kaliketek and Ferry Boat Routes and to find out the more effective path between the two. The method used in making decisions and selecting solutions is to use the AHP method. The results of this study include: Alternative value analysis is carried out by calculating pairwise comparisons starting from alternatives, sub-criteria and criteria. In this study, the calculated value of the sub-criteria was obtained with the GM value of each sub-criteria, namely time 0.93, convenience 0.88, cost 0.00 and safety 0.00. While the Vp value is obtained by dividing the GM value by the total GM value. And from this calculation the value of Vp time is 0.51, comfort 0.49, cost 0.00 and security 0.00. Then calculate the value of the evaluation criteria for the sub-criteria and get a GM value for the Kaliketek route of 0.79 while the ferry boat route is 0.81. The GM value is used to find the VP value by dividing each GM value by the total GM value. From the calculation, the VP value for the Kaliketek route is 0.49 and for the boat crossing route is 0.51. The choice of an alternative connecting route as a result of the construction of the Simo-Glendeng Bridge for 2 wheels is a boat route with a priority vector value of 0.51 and an emphasis on the time factor with a priority vector value of 0.51.